SINYAL PROFITABILITAS DAN REAKSI PASAR MODAL TERKAIT PENINGKATAN DIVIDEN SAAT LABA MENINGKAT - Tarsisius Renald Suganda; El Hezekiah Sabbat (Jurnal Keuangan dan Perbankan, 2014)
Dividend policy was a topic that still caused the pros and cons. Based on signaling theory, the announcementof dividend would be reacted by the market. The purposes of this study were to investigate the effect of thecompanys profitability as a result of dividend announcement, to examine the market reaction (using abnormalreturn and trading volume activity as the indicators) toward the announcement of dividend increase when theearning or profit was increasing. Event study method was used to answer the research questions. The resultshowed that there was a significant ROE decreasing in a year after the announcement. The market reactionshowed that there was a negative abnormal return during the period of the announcement of dividend increasewhen the earning or profit was increasing. The study also showed that the average trading volume wasinsignificantly increasing after the announcement. This study showed that the announcement indicated a badsignal for the Indonesian market. However, the findings of the research gave some suggestions for the sameresearches in Indonesia capital market.